The Effect of Cannabis sativa L. (Hemp Seed) on Hematological Parameters in Guinea Pigs - Karimi, Isaac; Hayatghaibi, Hossein; Yousefi, Javad; Saberivand, Adel; Zavareh, Saeed (Cardiovascular & Haematological Disorders - Drug Targets, 2007)
The objective of this study was to investigate the effect of ingestion of powder of hemp seed on blood picture. This study was experienced on five guinea pigs that fed with normal diet (fresh vegetable and tab water), in addition were force-fed 5 g/kg/day of the powder of hemp seed for 60 days by means of an endogastric tube and syringe. At the beginning day and the termination of study day-60 the blood was taken from animals and the erythrocyte number, leukocyte number, packed cell volume (PCV), and hemoglobin concentration values were determined. The result on analysis showed that erythrocyte-count and PCV significantly decreased (p < 0.05) whereas hemoglobin concentration and leukocyte number values showed a steady decline which was not significant (P > 0.05). None of the values fell below the normal physiological range of the experimental animals. This shows that hemp seed which contains tetrahydrocannabinols as its active constituents has long term significant toxicological implication such as bone marrow suppression with respect to the concentration given on the erythrocytes of mammals. It is recommended that individuals who have anemia or immunity complication should not use hemp seed in their food preparation on regular basis.
Keywords: Hemp seed